An assessment of the potential products and economic and environmental impacts resulting from a billion ton bioeconomy. (21st November 2016) - Rogers, Jonathan N.; Stokes, Bryce; Dunn, Jennifer; Cai, Hao; Wu, May; Haq, Zia; Baumes, Harry
Abstract: This paper is the summation of several analyses to assess the size and benefits of a Billion Ton Bioeconomy, a vision to enable a sustainable market for producing and converting a billion tons of US biomass to bio‐based energy, fuels, and products by 2030. Two alternative biomass availability scenarios in 2030, defined as the (i) Business‐as‐usual (598 million dry tons) and (ii) Billion Ton (1042 million dry tons), establish a range of possible outcomes for the future bioeconomy. The biomass utilized in the current (2014) (365 million dry tons) economy is estimated to displace approximately 2.4% of fossil energy consumption and avoid 116 million tons of CO2 ‐equivalent (CO2 e) emissions, whereas the Billion Ton bioeconomy of 2030 could displace 9.5% of fossil energy consumption and avoid as much as 446 million tons of CO2 equivalent emissions annually. Developing the integrated systems, supply chains, and infrastructure to efficiently grow, harvest, transport, and convert large quantities of biomass in a sustainable way could support the transition to a low‐carbon economy. Bio‐based activities in the current (2014) economy are estimated to have directly generated more than $48 billion in revenue and 285 000 jobs. Our estimates show that developing biomass resources and addressing current limitations to achieve a Billion Ton bioeconomy could expand direct bioeconomy revenue by a factor of 5 to contribute nearly $259 billion and 1.1 million jobs to the US economy by 2030. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd